2004
DOI: 10.3354/dao060247
|View full text |Cite
|
Sign up to set email alerts
|

Important disease conditions of newly cultured species in intensive freshwater farms in Greece: first incidence of nodavirus infection in Acipenser sp.

Abstract: We describe here the main pathological conditions of freshwater fish recently introduced for intensive rearing (open ponds and recirculating freshwater systems) in Greece. Sturgeon were susceptible to skeletal abnormalities of the spine (scoliosis and lordosis) of unknown aetiology. Horizontal transmission of nodavirus from infected sea bass to sturgeon was detected for the first time. This caused serious pathology and clinical signs, such as lethargy and imbalance, leading to secondary infections with Aeromon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 10 publications
0
39
0
6
Order By: Relevance
“…Larval or juvenile stages are more prone to this viral infection, but significant mortality can also occur in older fish up to production-size as in European seabass, sevenband grouper, humpback grouper Cromileptes altivelis and Atlantic halibut Hippoglossus hippoglossus [4,37,71,83,86,125]. Infections are also reported in freshwater fish, such as Chinese catfish (P. asotus); Australia catfish (Tandanus tandanus); Barramundi (L. calcarifer); Medaka (Oryzias latipes); guppy (Poicelia reticulata) and zebrafish (Danio rerio) [5,22,52,53,62,63,76]. Several experimental infection studies have demonstrated that both marine and fresh water finfish are susceptible to betanodavirus infection [23,38,39,52,53,63].…”
Section: Occurrence and Distributionmentioning
confidence: 99%
“…Larval or juvenile stages are more prone to this viral infection, but significant mortality can also occur in older fish up to production-size as in European seabass, sevenband grouper, humpback grouper Cromileptes altivelis and Atlantic halibut Hippoglossus hippoglossus [4,37,71,83,86,125]. Infections are also reported in freshwater fish, such as Chinese catfish (P. asotus); Australia catfish (Tandanus tandanus); Barramundi (L. calcarifer); Medaka (Oryzias latipes); guppy (Poicelia reticulata) and zebrafish (Danio rerio) [5,22,52,53,62,63,76]. Several experimental infection studies have demonstrated that both marine and fresh water finfish are susceptible to betanodavirus infection [23,38,39,52,53,63].…”
Section: Occurrence and Distributionmentioning
confidence: 99%
“…Οι Athanassopoulou et al (2003Athanassopoulou et al ( ,2004 ανί χνευσαν για πρώτη φορά τον ιό στην Ελλάδα σε ασθε νή λαβράκια που εκτρέφονταν σε γλυκό νερό, καθώς και σε οξΰρρυγχους με PCR, ενώ ο Jalil J., (2004, προ σωπική επικοινωνία) έχει αναφέρει συμπτώματα σε κέφαλο (Liza-auratus).…”
Section: εισαγωγηunclassified
“…από δυο διαφορετικά εντατικά συστήματα εκτροφής σε γλυκό νερό (Athanassopoulou et al, 2003) και σε εντα τικά εκτρεφόμενους οξΰρρυγχους (Athanassopoulou et al, 2004).…”
Section: Introductionunclassified
See 2 more Smart Citations